Separation of water-oil emulsion by using membrane - Yunan, M. H.; Yee, H. V.; Lee, H. L.; Ismail, A. F. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
Separation operation has to be done to get the crude oil, which is free of emulsion. Membranes are primarily used for separation and membrane processes are generally separation processes. Large-scale commercial uses of membrane separation have displaced conventional separation processes. Studies and testing had been performed on polysulphone flat sheet membrane crossflow ultrafiltration system. The effects of reject flowrate and feed pressure on the water-in-oil emulsion separation were observed. At constant flowrate, filtration rate and flux increase with pressure due to the effect of pressure difference across the membrane affects the presence of a higher strength to force the permeate to flow through the membrane. While at constant pressure, the higher the flowrate resulted in the higher filtration rate and flux due to the thinner cake layer build up on the membrane which decrease the resistance to the permeate stream to flow through the membrane. The purity of the permeate oil had been tested and has shown to be free of water.